Arts & humanities through the eras - Bleiberg, Edward I.; Gale Group (Detroit Thomson/Gale, 2005)
Profiling milestones and movements in the arts, literature, music and religion from a specific period, each volume in this set helps students and researchers understand the various disciplines of the humanities in relation to each other, as well as to history and culture. An overview of the period and a chronology of major world events begin each volume.
[1] Ancient Egypt (2675 B.C.E.-332 B.C.E.) / Edward Bleiberg, editor -- [2] Ancient Greece and Rome (1200 B.C.E.-476 C.E.) / James Allan Evans, editor -- [3] Medieval Europe (814-1450) / Kristen Mossler Figg and John Block Friedman, editors -- [4] Renaissance Europe (1300-1600) / Philip M. Soergel, editor -- [5] The age of Baroque and Enlightenment (1600-1800) / Philip M. Soergel, editor.
Electronic reproduction.
Keywords: Arts -- History; Civilization -- History; Electronic books